Understanding how older age drives decision‐making and outcome in Immune Thrombocytopenia. A single centre study on 465 adult patients. (8th November 2018) - Palandri, Francesca; Catani, Lucia; Auteri, Giuseppe; Bartoletti, Daniela; Fatica, Sofia; Fusco, Alessio; Bacchi Reggiani, Maria L.; Cavo, Michele; Vianelli, Nicola
Summary: We analysed the impact of older age on the management of immune thrombocytopenia (ITP) in 465 adult patients diagnosed between 1995 and 2017 and followed at our institution for a minimum of 12 months. Over a follow‐up of 4248 patient‐years, front‐line corticosteroids therapy was required in 334 patients (71·8%), mainly (85·3%) within 1 year from diagnosis. Need for first‐, second‐ and third‐line therapy was comparable in younger and older (age ≥65 years, n = 154) patients. Older patients presented more frequently with severe haemorrhages, started therapy with a higher platelet count and received lower dose front‐line corticosteroids; thereafter, they were preferentially treated with mild immunosuppressive therapies/thrombopoietin‐receptor agonists. Conversely, younger patients were more frequently treated with rituximab and splenectomy, achieving higher rates of complete responses. Incidence rates of ≥grade 2 complications were: 2·87 (haemorrhages), 1·55 (infections) and 0·66 (thromboses) per 100 patient‐years. Older age ( P = 0·01) and active haemorrhages at diagnosis ( P = 0·01) significantly predicted grade ≥2 haemorrhages during follow‐up. Older age ( P = 0·01), male gender ( P = 0·01), and thrombopoietin receptor agonist use ( P = 0·02) were significantly associated with a higher probability of thrombosis over time. Older age is a significant driver of diagnostic/therapeutic strategy in ITP resulting in different responses and complications rates.